Will Solvit and the Mummy's Curse. - Storm, Zed (UK Parragon, 2010)
Will Solvit is a regular ten year old - or so he thought. With the help of his dad's crazy inventions, Will finds himself on a real-life trip to Egypt. A cursed tomb and a temple full of zombie mummies are only the beginning of Will's adventures in this action-packed book. Featuring easy to read text and a cool decoder with 30 secret codes to crack, Will Solvit makes a great companion for middle readers. Be sure to check out the other titles in the Will Solvit series!
Include Illustrations
Keywords: Tombs -- Egypt -- Mummies